Potential of Polyphenolic Compounds in Rosella Flowers on Reducing Oxidative Stress and Inflammation After Exercise: A Systematic Review - Ayubi, Novadri; Padmasari, Dyah Fitria; Syafawi, Atika; Mario, Deby Tri; Ming, Jiang Wen; Aljunaid, Mohammed; Pranoto, Nuridin Widya; Komaini, Anton (Physical Education Theory and Methodology, 2024)
Study purpose. This study aims to analyze and highlight the potential of rosella flowers in reducing oxidative stress and inflammation after physical activity. Materials and methods. The study used a systematic review method by searching various journal databases such as Scopus, Web of Science, Pubmed and Embase. The inclusion criteria in this study were articles published in the last 5 years and articles discussing Rosella Flowers, Oxidative Stress, Free Radicals, Inflammation, and Exercise. The exclusion criteria in this research were articles published in disreputable journals. A total of 357 articles from the Scopus, Web of Science Pubmed and Embase databases were identified. A total of 8 articles that met the inclusion criteria were selected and analyzed for this systematic review. For standard operations, this study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) assessment. Results. The results of this systematic review research report that the flavonoid content found in rosella flowers has anti-oxidant and anti-inflammatory properties which have the potential to reduce oxidative stress and uncontrolled inflammation caused by physical activity and intense exercise. Conclusions. Rosella flowers show their ability as an anti-oxidative by donating hydrogen atoms to free radicals through phenolic compounds, thus breaking the cycle of ROS formation. The natural active ingredients in rosella flowers are able to reduce MDA and increase GSH which contributes to reducing oxidative stress and decreasing TNF-α which provides an anti-inflammatory effect in athletes after exercise.